Facial nerve branching pattern as seen in parotidectomy in Kashmiri population: our experience - Khaliq, Baba Aijaz; Nisar, Jasif; Yousuf, Aamir; Maqbool, Tabish; Ahmad, Rauf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: A prospective study to analyze the facial nerve branching pattern as seen in various parotidectomy surgeries in Kashmiri population. Main objective was to find out various branching patterns among peripheral branches of facial nerve in parotid tissue so that new young ENT surgeons could get benefited and it should be easy for them to perform parotid surgeries with less complications and unpredictable outcome. Methods: The prospective study was conducted in 35 patients undergoing superficial parotidectomy in our department of otorhinolaryngology GMC Srinagar over a period of one and half year. Facial nerve branching pattern was classified according to the description given by Davis et al. Branching pattern of main trunk was also observed in all cases. Results: The most common type of branching pattern of facial nerve in our study was type I seen in 12 (34.2%) patients, followed by type III seen in 9 (25.7%), followed by type II in 5 (14.2%), type IV in 4 (11.4%) patients, followed by type V in 3 (8.5%) and VI in 2 (5.7%). Conclusions: Type I branching pattern is the most common branching pattern of the facial nerve (34.2%) followed by type III (25.7%), following the pattern as described by Davis. Main trunk was found single in 32 (91.4%%) patients however in 3 (8.57%) patients trunk was dividing in 2 branches before dividing in peripheral branching pattern as described above.